Pengaruh Intellectual Capital Disclosure, Firm Size, dan Financial Leverage terhadap Tingkat Underpricing Saham - Isnaini, Fitria Rima; Oktavianna, Rakhmawati (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This study aims to analyze the effect of intellectual capital disclosure, firm size, and financial leverage on stock underpricing in cyclical consumer and non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2018-2023 period. The sample was collected using the purposive sampling method with several predetermined criteria, resulting in a research sample of 94 companies with a total of 122 data observations. This research obtained using the SPSS version 29 program shows that simultaneously the intellectual capital disclosure, firm size, and financial leverage variables have a significant effect on stock underpricing. Partially, intellectual capital disclosure and firm size affect the level of stock underpricing, while financial leverage do not affect the level of stock underpricing.